Analisis Evaluasi Strategi Pegadaian UPC Pasar Bumiayu Dengan SERVO Analysis - Seftiani, Afifah Tri; Isnaeni, Devit Ruman; Zuhwa, Unfah Ziyan; Shafrani, Yoiz Shofwa (FEB Universitas Maritim Semarang, 2025)
The study analyzes the business strategy of UPC Pegadaian Pasar Bumiayu using the SERVO approach (Strategy, Environment, Resources, Values, Organization). The findings indicate that Pegadaian has developed adaptive and innovative strategies through service digitalization, sharia-based products, as well as public education and strategic partnerships. Both internal and external environments are managed responsively, utilizing human resources and technology effectively. Organizational values promote a collaborative work culture and inclusive leadership. The evaluation shows that the SERVO approach helps Pegadaian remain competitive and relevant in the modern financial industry.